Work Ethos Framework towards Work-Life Balance. - Wan Azli , Wan Saudah; Anas, Norazmi; Mohd Noor , Ahmad Firdaus; Muhamad Ramlan , Anaztasia Natasha (Journal of Islamic, Social, Economics and Development, 2025)
In accordance to the 2024 Global Work-Life Balance Index, Malaysia maintains the second least favorable work-life balance worldwide. Excessive workload overwhelms Malaysians, which ensues to inadequate rest, scarcity of time spent on personal and familial time which eventually influence feelings of life fulfillment in general. Therefore, constructing a conceptual framework known as the RAHMAH Work Ethos Framework for Work-Life Balance is the primary objective of this research. The investigation utilizes a qualitative case study approach. A thorough work culture that serves as the basis for the proposed model was established through a literature review that utilized document analysis to incorporate components of Islamic work ethics into the RAHMAH paradigm. The results highlight six aspects of Islamic ethics at work: taqwa (God-consciousness), amanah (trustworthiness), integrity, ihsan (excellence), discipline, and itqan (perfection in work). Conversely, the RAHMAH tenets promote compassion, tranquility, balance, hospitality, authenticity, and respect. Confluence of the two develops a thorough work culture that boasts outstanding output, worship-based work ethics, harmonious relationships, employee satisfaction, and corporate loyalty. This research endeavor is additionally anticipated to bring forth a theoretical and practical contribution towards establishing an ethical, humanistic, and spiritually driven working atmosphere across workplace organizations. In fostering a workplace that strikes an equitable equilibrium between worldly necessities and spiritual goals, it likewise assists policymakers, employers, educators, and Muslims. It is expected that following the RAHMAH ethos framework will facilitate the development of a more compassionate, professional, and thriving community at large, which is consistent with the desired outcomes of Malaysia MADANI.